Historical aspects of competence-based paradigm implementation in the process of headmasters’ training - Chebotarova, I. O. (Problems of Engineer-Pedagogical Education, 2018)
The present work highlights various historical aspects of competence-based approach implementation in the national and foreign educational systems. Our research has revealed that competence-based approach made the way from behavioural interpretation of educationfrom getting the necessary stimulation response to its contemporary understanding like a constant competence forming, necessary for the successful existence in the conext of information-oriented society. We paid a special attention to the change of its essential defenitions content interpretation, changes of headmsters’ functions and tasks in the framework of the competence-based approach. It was explored that scientists from different countries split over the definitions of the moments of the competence-based approach, in particular regarding of competence quantity and structure, which includes standard competences. At the same time, it should be emphasized that lately unification trend of these categories is observed. The undertaken study showed that educational modernization is a constant process.